Primitive Tumour of the Pulmonary Valve: Discussion of the Differential Diagnosis - A. Hannecart; D. Ndjekembo-Shango; F. Vallot; O. Simonet; M. De Kock (Case Reports in Critical Care)
There is a paucity of information concerning cardiac tumours of the pulmonary valve due to their rarity at this location. We report a case of a 47-year-old patient suffering from haemoptysis, asthenia, and acute kidney injury (AKI). A transthoracic echocardiography (TTE) revealed a mass on the pulmonary valve. Further diagnostic investigation was completed until he exhibited worsening hemodynamic instability. This case emphasizes the lack of information regarding the management of a pulmonary valve tumour.